2020
DOI: 10.1186/s12884-020-2742-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeted antenatal anti-D prophylaxis for RhD-negative pregnant women: a systematic review

Abstract: Background: All non-sensitized Rhesus D (RhD)-negative pregnant women in Germany receive antenatal anti-D prophylaxis without knowledge of fetal RhD status. Non-invasive prenatal testing (NIPT) of cell-free fetal DNA in maternal plasma could avoid unnecessary anti-D administration. In this paper, we systematically reviewed the evidence on the benefit of NIPT for fetal RhD status in RhD-negative pregnant women. Methods: We systematically searched several bibliographic databases, trial registries, and other sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Recently, data from about 60.000 study participants were pooled in a large meta-analysis for the purpose to determine the diagnostic accuracy of NIPT RhD [20]. However, in this systematic review, only studies were included, which evaluated lab developed (in-house) tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, data from about 60.000 study participants were pooled in a large meta-analysis for the purpose to determine the diagnostic accuracy of NIPT RhD [20]. However, in this systematic review, only studies were included, which evaluated lab developed (in-house) tests.…”
Section: Discussionmentioning
confidence: 99%
“…Since the feasibility of targeted antenatal RAADP based on the result from a NIPT for the prediction of the fetal RhD status has been proposed by Dennis Lo's group and a Dutch group in 1998 it took about 12 years until the first nationwide program for targeted RAADP was implemented in Denmark [11][12][13]. Until today many validation studies have been published and extensively reviewed which revealed an excellent diagnostic accuracy of NIPT for RhD [14][15][16][17][18][19][20][21]. It has to be stressed in the given context that only false-negative NIPT RhD results may have relevant consequences (i.e., increased risk for anti-D alloimmunisation).…”
Section: Introductionmentioning
confidence: 99%
“…Such a policy has recently been introduced into clinical practice in countries such as Denmark, the Netherlands, and the United Kingdom. A recent meta‐analysis of 60 000 participants showed that it has a very high sensitivity (99.9%; 95% CI, 99.5%–100%) and specificity (99.2%; 95% CI, 89.5%–99.5%) as compared with testing newborn's blood 21 . First‐trimester non‐invasive Rh(D) typing may therefore be used to prevent unnecessary administration of anti‐Rh(D) immunoglobulin in the course of pregnancy (routinely or following amniocentesis, etc.).…”
Section: Noninvasive Fetal Rh(d) Typing In the First Trimestermentioning
confidence: 99%
“…Presence of the fetal RHD gene indicates that the fetus is RhD positive. Since the first reports of cell-free fetal RHD in maternal plasma [16,17], noninvasive fetal RHD genotyping has become highly integrated into clinical medicine, and its accurate performance has been covered comprehensively in the literature [12,13,[18][19][20][21][22][23][24].…”
Section: Antenatal Rhd Screeningmentioning
confidence: 99%